Information avoidance: self-image concerns, inattention, and ideology - Momsen, Katharina; Ohndorf, Markus (Journal of economic behavior & organization, 2023)
We report the results of an experiment on willful information avoidance regarding measures to address Covid-19. In the experiment, participants choose between two options, each associated with a contribution to the Corona Fund of the Red Cross USA and a payment to the participant. Depending on the treatment, either the participants’ payoff, the donation, both or none of these pieces of information were hidden, but revealable. With this design, we can separate motivated reasons for ignorance from non-motivated reasons, both of which are present in our data. Furthermore, we find evidence of both self-serving and pro-social information avoidance. These behavioral patterns correlate with the subjects’ political attitudes: while voters of the Democratic Party are prone to exhibit pro-social information avoidance, Republican voters rather engage in self-serving information avoidance.
Online veröffentlicht am 18. Mai 2023
Gesehen am 19.12.2023